The Effect of Guided Play on Early Literacy Skills in Muaro Jambi Kindergarten Children - Sarinem Sarinem; Della Amrina Yusra (International Journal of Multidisciplinary Sciences and Arts, 2026)
Early literacy is a critical foundation for young children’s academic development that determines lifelong learning success. This research is motivated by the low early literacy ability of Group A children at TK Al-Azhar, Muaro Jambi Regency, indicated by limited letter recognition, phonemic awareness, and vocabulary. This study aims to analyze the effect of the Guided Play strategy on early literacy abilities of Group A children at TK Al-Azhar, Muaro Jambi Regency. The method used is a quasi-experimental approach with a pretest-posttest nonequivalent control group design. The research sample comprised 40 children, consisting of 20 in the experimental group and 20 in the control group. The research instrument was an early literacy observation sheet with 20 indicators. Data analysis techniques included Shapiro-Wilk normality test, Levene’s homogeneity test, and Paired Sample t-Test. The results showed a significant improvement in early literacy ability in the experimental group, with the pretest mean score of 44.75 increasing to 74.85 in the posttest. The Paired Sample t-Test yielded t = -18.392 with Sig. (2-tailed) = 0.000 < 0.05. Therefore, H0 is rejected and Ha is accepted, indicating that the Guided Play strategy significantly affects early literacy ability of Group A children at TK Al-Azhar, Muaro Jambi Regency. This study recommends the systematic application of the Guided Play strategy in literacy learning at the early childhood education level.